Cooperation of patient as key factor to overcome oral habits - Magdalena Lesmana (Dental Journal (Majalah Kedokteran Gigi), 2009)
Introduction: Orthodontic treatments have developed rapidly on the last decade even though; the sophisticated treatment has been limited by patient’s behavior. Orthodontist should acknowledge that the success of treatment not only depends on the knowledge and skill of the operator, but on the patient’s behavior as well, which is very critical to overcome the oral habit, including anterior tongue thrust swallow (ATTS). Patient’s cooperation is the key factor to set prognosis of oral habit correction and have to be proven through analysis of questioners. Methods: Patient cooperation scale (PCS) was made for this research involving 68 orthodontic patients for correction of ATTS from Faculty of Dentistry Indonesia University and Ladokgi as respondents. PCS assessment was based on data sets of: Patient awareness of ATTS (PAw), Patient Acceptance to receive treatment (PAc), and Patient Comfortable for using appliances (PC). The evaluation was obtained by calculation the total score of 10 items from each component, which gave 0–30 range of scale and would be 0–90 range of cooperation scale as the final result. Result: PCS assessment can be based on data sets of PAw, PAc, and PC. It is valid and reliable. The score for the cooperative patients range between 0–25. The higher the score from this questionnaire shows less cooperation from respondent. On the other hand, the lower the score showed better cooperation. Conclusion: PCS can be used for the prognosis of the successful oral habits correction and has a significant relation with the length of successful treatment.